SELECTED ECONOMIC ASPECTS OF THE BANKING CRISIS - BONDARENKO, ANASTASIA; GUSAREVA, NADEZDA; LOKTIONOVA, YULIA; EVDOKIMOVA, YULIA; MELNIK, MIKHAIL; SHINKAREVA, OLGA; YANINA , OLGA (International Journal of Psychosocial Rehabilitation, 2020)
The subject of this work is the problems and trends of occurrence and development of the crisis of the Russian banking system, as well as a set of financial and economic relations and general cause-and-effect relationships that form the conditions for their development. Objectives of the study: to investigate the problems of the Russian banking system, which led to the crisis in the banking sector; to identify the main risks of the growth of crisis phenomena and some ways to prevent them. The study is based on the aspect approach using monographic and analytical methods. The study reveals the main risks of the crisis phenomena growth and some ways to prevent them, as Russia is currently experiencing another banking crisis. The study showed that the main threat to the stability of the Russian banking system are the risk of political interference, tougher sanctions by the United States, the risk of emerging markets. A key indicator of the stability of the banking system is the trust of the population and the interaction of banks with customers through social networks.